Globalised diet patterns in Mediterranean: the evidence of the cooking wares from Aquileia (UD), Italy - Dobreva, Diana; Riccato, Anna; Bellini, Martina Trivini (Rei Cretariae Romanae Fautorum Acta, 2022)
It has become increasingly apparent over the last decades that cooking pottery played a considerable role as a trade commodity in ancient time. By taking a closer look at the pottery found in Aquileia, we want to explore and discuss the relationship between locally produced and imported cooking wares from a quantitative, morphological and functional point of view. We will make use of case studies from the so-called domus of Titus Macer to establish in which ways this correlation changes over time and how we can explain some trends. The possibility to examine domestic contexts offered the opportunity to carry out an in-depth analysis of the cooking ware in order to reconstruct pottery sets and, as far as possible, eating habits and food practices.